EDUCATION OF PUPILS’ COGNITIVE SKILLS THROUGH APPLICATION OF VIRTUAL AND REAL EXPERIMENTS IN CHEMISTRY LESSONS (The Doctoral Dissertation of Roman Voronovič) - Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2013)
...